Calpain Determines the Propensity of Adult Hippocampal Neural Stem Cells to Autophagic Cell Death Following Insulin Withdrawal. (14th July 2015) - Chung, Kyung Min; Park, Hyunhee; Jung, Seonghee; Ha, Shinwon; Yoo, Seung‐Jun; Woo, Hanwoong; Lee, Hyang Ju; Kim, Seong Who; Kim, Eun‐Kyoung; Moon, Cheil; Yu, Seong‐Woon
Abstract Programmed cell death (PCD) has significant effects on the function of neural stem cells (NSCs) during brain development and degeneration. We have previously reported that adult rat hippocampal neural stem (HCN) cells underwent autophagic cell death (ACD) rather than apoptosis following insulin withdrawal despite their intact apoptotic capabilities. Here, we report a switch in the mode of cell death in HCN cells with calpain as a critical determinant. In HCN cells, calpain 1 expression was barely detectable while calpain 2 was predominant. Inhibition of calpain in insulin‐deprived HCN cells further augmented ACD. In contrast, expression of calpain 1 switched ACD to apoptosis. The proteasome inhibitor lactacystin blocked calpain 2 degradation and elevated the intracellular Ca2+ concentration. In combination, these effects potentiated calpain activity and converted the mode of cell death to apoptosis. Our results indicate that low calpain activity, due to absence of calpain 1 and degradation of calpain 2, results in a preference for ACD over apoptosis in insulin‐deprived HCN cells. On the other hand, conditions leading to high calpain activity completely switch the mode of cell death to apoptosis. This is the first report on the PCD mode switching mechanism in NSCs. The dynamic change in calpain activity through the proteasome‐mediated modulation of the calpain and intracellular Ca2+ levels may be the critical contributor to the demise of NSCs. Our findings provide a novel insight into the complex mechanisms interconnecting autophagy and apoptosis and their roles in the regulation of NSC death. Stem Cells2015;33:3052—3064